Antecedents of Customer Satisfaction Towards Chatbot on Used Car Buying and Selling Platforms in Indonesia - Panjaitan, Hapizin Yonani; Risqiani, Renny (APMBA (Asia Pacific Management and Business Application), 2024)
This research aimed to examine the impact of chatbot service quality, perceived value, cognitive trust, and affective trust on customer satisfaction within the used car buying and selling platforms in the largest metropolis area in the Indonesian capital, namely Jabodetabek region. This research study using a quantitative approach, and involved 268 participants who met the specified criteria. The data analysis and hypothesis testing were conducted using SEM PLS. The findings revealed that the service quality of chatbot significantly influences perceived value, cognitive trust, and affective trust. However, it does not exert a direct impact on customer satisfaction. Notably, perceived value demonstrated a positive correlation with customer satisfaction and acted as a mediator in the positive relationship between chatbot service quality and customer satisfaction. Moreover, cognitive trust was identified as a factor positively affecting customer satisfaction and played a mediating role in the positive connection between chatbot service quality and customer satisfaction. On the other hand, affective trust was found to lack a direct positive impact on customer satisfaction and did not mediate the positive influence of chatbot service quality on customer satisfaction.